Precipitation variations of western equatorial pacific during glacial–interglacial cycles since MIS8: Evidence from multi–proxies of abyssal sediment - Wang, Genmin; Xu, Jishang; Jiang, Zhaoxia; Li, Guangxue; Zhang, Yang; Zhang, Wenchao; Liu, Yong (Frontiers in Earth Science, 2023)
As an important global water vapor source, the Western Pacific warm pool (WPWP) influences precipitation changes in the middle and low latitudes. The low-latitude water cycle is a key climate parameter at different time scales, as it contributes to various feedback processes. However, at present, indicators of precipitation variability in the equatorial western Pacific are limited. In this work, we used the sedimentary record of the southern margin of the WPWP to study the precipitation variability over the western equatorial Pacific since MIS8. The age framework based on plankton-foraminifera δ18O was used to analyze changes in geochemical elements, clay minerals, and magnetic parameters of a marine sediment core H10. As new precipitation records, our precipitation records (TiO2, χ, and SIRM concentration without carbonate base) are closely related to monsoon and Intertropical Convergence Zone and generally in inverse phase with the oxygen isotope records of stalagmites from caves in China. A spectral analysis showed an obvious precession period. The southern margin of the WPWP water cycle is closely related to the East Asian monsoon in the last four climate cycles, and is influenced by both high and low latitudes.